2009
DOI: 10.1007/dcr.0b013e3181a79575
|View full text |Cite
|
Sign up to set email alerts
|

Nonreversal of Hartmann's Procedure for Diverticulitis: Derivation of a Scoring System to Predict Nonreversal

Abstract: More than 30% of patients undergoing a Hartmann's procedure for diverticulitis will not have their stoma reversed within a year. If this scoring system can be validated in an independent group of patients, it will be useful in allowing surgeons to strategize accurately and to counsel patients realistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
5
18
0
Order By: Relevance
“…Postoperative blood transfusion was another independent predictor of non-restoration of intestinal continuity in our series. A similar result was reported by Riansuwan et al [7] and Vaid et al [8]. We suggest that patients who did not require blood transfusion had fewer comorbidities or a benign pathology, or a technically easier procedure.…”
Section: Discussionsupporting
confidence: 91%
“…Postoperative blood transfusion was another independent predictor of non-restoration of intestinal continuity in our series. A similar result was reported by Riansuwan et al [7] and Vaid et al [8]. We suggest that patients who did not require blood transfusion had fewer comorbidities or a benign pathology, or a technically easier procedure.…”
Section: Discussionsupporting
confidence: 91%
“…3,5,14 Riansuwan et al studied patients undergoing a Hartmann's procedure for diverticulitis only and multivariate analysis demonstrated significance for POSSUM score, preoperative transfusion, pulmonary co-morbidity, pneumaturia, perforation and anticoagulation as independent predictors for reversal within 12 months. 7 While we found benign disease to be a significant factor on univariate analysis, it was not significant on multivariate analysis. We performed 96 Hartmann's for diverticulitis from a total of 707 admissions for diverticulitis (unpublished data) but subgroup analysis of this cohort did not produce any other significant findings.…”
Section: Discussionmentioning
confidence: 60%
“…7 There is some debate regarding the optimum timing for reversal of Hartmann's, with Pearce et al making a convincing argument for waiting 6 months suggesting that improvements in the patient's fitness, fatigability, nutrition, as well as less adhesions. 12 However Wigmore et al demonstrated an acceptable morbidity and mortality with 50% and 80% of patients reversed within 3 and 6 months respectively, thus restoring bowel continuity earlier.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[3][4][5] Once performed it is possible to restore intestinal continuity at a later date with a reversal of Hartmann procedure (RHP), but this is in itself associated with not inconsiderable perioperative risk. 2,7,8 If complication rates after RHP could potentially be reduced, then it is likely that the number of reversal procedures will increase and the percentage of patients left with a permanent stoma will decline as a result. A recent study that reviewed nationwide trends in the use of Hartmann procedure and RHP in the United Kingdom showed that only 23% of patients had their stoma reversed in a 4-year period after their primary operation.…”
mentioning
confidence: 99%